Calcium Phosphate and Silicate-Based Nanoparticles: History and Emerging Trends - van Rijt, Sabine; de Groot, Klaas; Leeuwenburgh, Sander C G (Tissue engineering. Part A, 2022)
Calcium phosphates (CaPs) and silicate-based bioglasses have been extensively studied since the early 1970s due to their unique capacity to bind to host bone, which led to their clinical translation and commercialization in the 1980s. Since the mid-1990s, researchers have synthesized nanoscale CaP and silicate-based particles of increased specific surface area, chemical reactivity, and solubility, which offer specific advantages compared to their bulk counterparts. This review provides a critical perspective on the history and emerging trends of these two classes of ceramic nanoparticles. Their synthesis and functional properties in terms of particle composition, size, shape, charge, dispersion, and toxicity are discussed as a function of relevant processing parameters. Specifically, emerging trends such as the influence of ion doping and mesoporosity on the biological and pharmaceutical performance of these nanoparticles are reviewed in more detail. Finally, a broad comparative overview is provided on the physicochemical properties and applicability of CaP and silicate-based nanoparticles within the fields of (i) local delivery of therapeutic agents, (ii) functionalization of biomaterial scaffolds or implant coatings, and (iii) bioimaging applications.